In situ fabrication of Si3N4/SiC nanocomposite using a commercial polymer - Kim, CS; Oh, YS; Cho, WS; Lim, DS; Cheong, DS (ELSEVIER SCIENCE SA, 1998)
Si3N4/SiC nanocomposite has been prepared using a chemical reaction between Si3N4 powder and phenolic resin as a commercial polymer. The polymer was an effective source that could provide free carbon for fabrication of the nanocomposite. In mixture containing both the Si3N4 powder, which contained some amount of SiO2, and the polymer, SiC nanoparticles were considered to be formed by direct reaction between carbon and Si3N4/SiO2. Sizes of the formed SiC particles were in the range of 10-200 nm. The SiC particles were well dispersed in the matrix. (C) 1998 Elsevier Science S.A.
Keywords: MECHANICAL-PROPERTIES; SILICON-CARBIDE; CARBON-FILMS; PRECURSORS; CERAMICS; MICROSTRUCTURE; PYROLYSIS; COMPOSITE